Ta'dib: Character Foundations in the Perspective of Syed Muhammad Naquib Al-Attas - Raden Rizky Fahrial Ahmad; Reza Aditya Ramadhani; Roibin roibin; Dila Rukmi Octaviana; Syuhadak syuhadak (At-Ta'dib, 2023)
The concept of Ta'dib, pioneered by Al-Attas, serves as a suitable guidance in shaping students' characteristics, encompassing not only morality but also individual development rooted in natural and spiritual values. This study aims to explore the concept of Ta'dib proposed by Syed Muhammad Naquib Al-Attas in the formation of students' character. The research adopts a descriptive qualitative approach through a literature review, employing an in-depth philosophical analysis. Primary sources include Al-Attas' books, while secondary sources consist of journal articles, books, and related research materials. Data collection involves gathering Al-Attas' manuscripts, books, and relevant journals, followed by data analysis by scrutinizing the contents of various manuscripts and books to draw conclusive findings. The findings reveal that the integration of earlier principles into character development offers a valuable opportunity to harmonize knowledge acquisition and ethical behavior within students. Consequently, it enables them to contribute to society by performing virtuous acts and exhibiting good conduct, supported by a steadfast foundation of faith.